PENGARUH RELATIONSHIP MARKETING DAN KEPERCAYAAN KONSUMEN TERHADAP MINAT BELI ALBUM K-POP TREASURE (STUDI KASUS PADA KOMUNITAS PENGGEMAR ALBUM TREASURE DI JAKARTA) - Adinda Dwifadhilah; Lukman Nul Hakim (JAMBIS : Jurnal Administrasi Bisnis, 2021)
This study aims to determine the effect of Relationship Marketing and Consumer Trust on BuyingInterest among the community of fans of the album ‘Treasure’ in Jakarta.. The research methodused was a quantitative method. Data collection was done through the distribution ofquestionnaires. The population in this study were fans of the K-Pop album ‘Treasure’ in Jakarta.The sampling technique used was nonprobability sampling with purposive sampling method andthe Hair.et.al formula, where a sample is taken at least 5 times from the number of questions itemscontained in the questionnaire. The result was a sample consisting of 130 respondents (26x5). Thecollected data were analyzed using multiple linear regression analysis with the help of the IBMSPSS Statistics Version 28 Program.. The results showed that: (1) Relationship Marketing had apositive and significant effect of Buying Intrest, with an influence value 31,4; (2) Consumer Trusthas a positive and significant effect on Buying Interest, with an influence value of 28,1%; (3)Relationship Marketing and Consumer Trust simultaneously have a positive and significant effecton Buying Interestm with an influence value of 34,5%, of which the remaining 65,5% is influencedby other factors not included in this study.